Immobilization of Heavy Metals in Natural Zeolite-blended Cement Pastes. (2016) - Vyšvařil, Martin; Bayer, Patrik
Abstract: The toxic wastes containing heavy metals are conducive to serious environmental problems at the contamination of water, air and soil. The ability of alumino-silicate systems to immobilize heavy metals from hazardous wastes by solidification process has been investigated since 1990s. Likewise, the efficiency of zeolites to fix heavy metals in their frameworks has relatively long been known. This paper deals with the investigation of efficiency of natural zeolite-blended cement pastes for the immobilization of heavy metals. Natural zeolite was used to partially replace ordinary Portland cement (OPC) at rates of 0% and 20% by weight of a binder and soluble heavy metal salts were added to a mixing water in an amount of 1% and 5% by weight of the binder. The flexural and compressive strength of the cement pastes were investigated, while the leachability of the heavy metals was determined. Additionally, scanning electron microscopy was performed to investigate the microstructure of the cement pastes, while the pore size distribution was analyzed with mercury intrusion porosimetry. The results indicated that the flexural and compressive strengths of the pastes containing 20 wt.% of natural zeolite were higher than those with OPC alone. It was also found out that the effectiveness in reducing the leachability of Ba, Cd, Cu, Ni and Pb was better for the natural zeolite-blended cement pastes.